Amplification of 3q26.2, 5q14.3, 8q24.3, 8q22.3, and 14q32.33 Are Possible Common Genetic Alterations in Oral Cancer Patients - Ambele, Melvin A.; van Zyl, Andre; Pepper, Michael S.; van Heerden, Marlene B.; van Heerden, Willie F. P. (Frontiers in Oncology, 2020)
The lack of clinical biomarkers for head and neck cancer subtypes limits early diagnosis and monitoring of disease progression. This study investigates genetic alterations in clinically identical tumor, tumor-adjacent dysplastic epithelium (TADE) and normal epithelium (NE) in five oral cancer patients to identify differences and commonalities between oral cancer, TADE and NE. A VELscope®Vx device was used to identify TADE and NE surrounding a clinical tumor for analysis of genetic alterations using the OncoScan® assay. One of the tumor samples examined was an “M” class tumor with a high confidence BRAF:p.G469A:c.1406G>C somatic mutation, which is the first to be reported in oral cancer. Another tumor showed mosaicism in genetic alterations, indicating the presence of multiple clones. Overall, each patient’s tumor, TADE and NE showed a distinct genetic profile which indicates intertumoral clonal/genetic diversity. Interestingly, four tumors showed gain of 3q26.2, 5q14.3, 8q24.3, 8q22.3, 14q32.33 and loss/LOH in 9p21.3 while all TADE had LOH on 22q11.23. In addition, some genetic alterations progressed from NE through TADE into tumor in individual patients. Furthermore, no molecular event was identified that is common to all NE and/or TADE that progressed into tumor. This pilot study demonstrates the presence of genetic heterogeneity in oral tumorigenesis, and suggests that there might exist some common genetic alterations between tumors and TADE. However, this observation would need to be further investigated and validated in a larger cohort of oral cancer patients for its potential role in oral tumorigenesis.